2021
DOI: 10.3390/app112211060
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Fires: Multi-Channel Deep Learning Models for Wildfire Severity Prediction

Abstract: Wildfires are one of the natural hazards that the European Union is actively monitoring through the Copernicus EMS Earth observation program which continuously releases public information related to such catastrophic events. Such occurrences are the cause of both short- and long-term damages. Thus, to limit their impact and plan the restoration process, a rapid intervention by authorities is needed, which can be enhanced by the use of satellite imagery and automatic burned area delineation methodologies, accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 67 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…These findings agree with previous studies using satellite imagery (Landsat and Sentinel 2), showing that machine learning classifiers are well suited to the broad-scale mapping of fire severity with remotely sensed imagery [48,72,73]. However, even the most recent studies are not sensitive to local scale and spatial patchiness [74,75].…”
Section: Discussionsupporting
confidence: 91%
“…These findings agree with previous studies using satellite imagery (Landsat and Sentinel 2), showing that machine learning classifiers are well suited to the broad-scale mapping of fire severity with remotely sensed imagery [48,72,73]. However, even the most recent studies are not sensitive to local scale and spatial patchiness [74,75].…”
Section: Discussionsupporting
confidence: 91%
“…The experiment results showed that the Double-Step U-Net with BCE loss achieved the best MSE of 0.54. Monaco et al [147] also developed a two-step CNN solution to detect burned areas and predict their damage on satellite data. First, a binary semantic segmentation method-based CNN was used to detect burned areas, and then a regression method-based CNN was applied to predict their damage severity between 0 (no damage) and 4 (completely destroyed).…”
Section: Deep Learning-based Approaches For Fire Susceptibility Using...mentioning
confidence: 99%
“…Using a satellite image collected from Copernicus EMS, DS -UNet, and DS-UNet++ models with BCE loss showed a higher IoU of 75% and 74%, respectively, in delineating the burnt areas compared to DS-AttU and DS-SegU; DS-AttU, DS-UNet, and DS-UNet++ performed better in predicting the damage severity levels of burned areas, obtaining an RMSE of 2.429, 1.857, and 1.857, respectively. Monaco et al [149] also used DS-UNet to detect wildfire and to predict the damage severity level, from 0 (no damage) to 5 (completely destroyed) on Sentinel-2 images. DS-UNet achieved an average RMSE of 1.08, overcoming baseline methods such as DS-UNet++, DS-SegU, UNet++, PSPNet, and SegU-Net.…”
Section: Deep Learning-based Approaches For Fire Susceptibility Using...mentioning
confidence: 99%
“…Environmental science examples: Attention-based methods have already found application for precipitation mapping (Sønderby et al, 2020;Espeholt et al, 2022), estimating visibility due to coastal fog (Kamangir et al, 2021), generating super-resolution imagery (Liu et al, 2018), wildfire estimation (Monaco et al, 2021), population density estimation (Savner and Kanhangad, 2023), damage assessment (Hao et al, 2021), and land cover estimation (Ghosh et al, 2021;Wang and Sertel, 2021). Many additional examples are provided in the following section.…”
Section: A New Generation Of Neural Networkmentioning
confidence: 99%